PERTUNJUKAN TAYUB SEBAGAI SARANA RITUAL PERNIKAHAN DI TUNJUNG SEMI MLALE JENAR SRAGEN - Eko Wahyu Prihantoro (Gelar : Jurnal Seni Budaya, 2012)
Mlale Village, Sub District Jenar, District Sragen has a unique tradition, namely a ritual conducted  by a local community. This ritual is held to celebrate a wedding ceremony by performing Tayub. This research aims to:  a) describe the wedding ceremony at Mlale Village by performing Tayub as its ritual means, b) interprete the meaning of movements  and melody (gendhing) in Tayub dance. The style of this research is interpretative description of a qualitative nature. The first step in this research is data collection through field study, observation,and interviews, and the second step is data processing by analyzing qualitatively the form, function and meaning. Those steps are applied consecutively beginning from reduction, data reformation or display, and ending in conclusion. This research uses a holistic approach involving all aspects in performing art. The research results show that  the performance is meant as a gratitude and request  to God hoping that  wedding will  last eternally,  and be blessed, be protected against disturbance, be granted all desire, have a child  and happiness. Key words : ritual, Tayub, meaning, Sragen